The Development of Project-Based Learning Method to Increase Students' HOTS in Mathematics - Nurmawati Nurmawati; Sri Kadarwati; Eko Andy Purnomo; Agung Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The highest level of the cognitive process hierarchy is Higher-Order Thinking Skill (HOTS). HOTS allows students to solve challenges, but time for processing is limited. Based on the findings in the field, many students do not have the skills related to HOTS. Based on these findings, developing a learning model that can increase HOTS in students is necessary. One of the learning models that can improve HOTS is the project-based learning model (PjBL). This study aimed to produce a project-based learning model for improving HOTS. This type of research is on developing a 4-D model developed by Thiagarajan, Semmel, and Semmel with modifications. The subject of this research is a project-based learning model. The instruments used were a needs analysis sheet, material analysis and PjBL model validation sheets. Methods of data collection by observation, questionnaires and interviews. The research results show that the project-based learning model has met the valid criteria for increasing HOTS.